Methods in HPV Surveillance: Experiences from a Population-Based Study of HP V Infection among Women in the San Juan Metropolitan Area of Puerto Rico - Ortiz, Ana Patricia; Marrero, Edmir; Muñoz, Cristina; Pérez, Cynthia M.; Tortolero-Luna, Guillermo; Romaguera, Josefina; Rodríguez, Nahir; González-Falero, Andrea; Palefsky, Joel; Suárez, Erick (Puerto Rico Health Sciences Journal, 2015)
This article describes the methodology of the first population-based study of human papillomavirus (HP V) infection among women aged 16-64 years residing in the San Juan Metropolitan Area of Puerto Rico (PR). The sample was identified through a complex sampling design of households. The sampling frame was selected in four stages, using census tracts maps from the Census Bureau. Women completed a face-to-face interview and a computer-assisted self-interview using the Audio CASI system, for the collection of demographic, clinical, and lifestyle variables, and sampling acceptability. Anal, cervical, and oral specimens were collected through self-collection methods for HP V DNA testing using a modified pool of MY09/MY11 consensus HP V L1 and human ß-globin amplification primers. Anthropometric measurements were taken using the Third National Health and Nutrition Examination Survey methodology. Blood samples were collected to create a bio-repository for future HP V-related studies. Fifty census tract blocks were randomly selected. We recruited 566 women, with a response rate of 83.4%. Response rates did not vary by age-group (p>0.05); although they varied by socioeconomic (SES) census block stratums (p<0.05), response rates were good (>75%) in all SES strata. All participants agreed to respond to the surveys and provide the requested anogenital and oral samples. Overall, more than 98% understood and more than 50% felt comfortable with the cervical, anal, and oral self-collection methods used. This article documents the feasibility of performing population-based studies for HP V surveillance in women in PR.